EFEITO DO SEXO SOBRE O DESEMPENHO PRODUTIVO DE FRANGOS DE CORTE COBB 500® NA FASE FINAL (35-42 DIAS) - Reis, Bruno; Galuci, Andréia; Gottardi, Camila Priscila; De Souza, Aurélio Ricardo; Dos Santos, João Paulo; Oliveira, Fernando (ANAIS DO ENIC, 2018)
-